“RED” COLOR IN ARMENIAN AND RUSSIAN LINGUOCULTURES. - GRDZELYAN, ROUZAN (Bulletin of Yerevan University H: Russian Philology, 2020)
The article is devoted to the study of red color names in Armenian and Russian linguocultures – methods for studying color meanings, synonymy, combinability features, linguistic and cultural characteristics, and the features of red color verbalization.